Laparoscopic Transanal Endoscopic Microsurgery via Single-Port: A Case Report - Gonultas, Fatih; Koc, Cemalettin; Hatipoglu, Sinan; Yonder, Huseyin; Karakas, Serdar; Ates, Mustafa; Dirican, Abuzer (Annals of Medical Research, 2021)
None